BACTERICIDAL ASSESSMENT OF TWO SUBGINGIVAL IRRIGATION SOLUTIONS USED IN PERIODONTAL DISEASE - Anca Stupu; Ioana Rudnic; Alexandra Martu; Diana Nitescu; Ovidiu Nicolaiciuc; Sorina Solomon (Romanian Society of Oral Rehabilitation, 2014)
Introduction Based on microbial etiology of chronic periodontitis, local microbial agents impact and systemic chemotherapy have been used to improve the effectiveness of scaling and root planing. Povidone-iodine ( polyvinylpyrrolidone-iodine ) is one of the most widely used antiseptic agents in the medical field. It is used as a disinfectant for the skin, hands and mucous membranes. It can also be used for the treatment of wounds rinsing body cavities, joints and ophthalmic applications. It is comprised of a combination of water-soluble polymer, povidone and iodine. Aim of the study This study aimed to evaluate the composition of the microbial flora in patients with various forms of periodontal disease and to study the bactericidal effect of the two antiseptic: chlorhexidine solution of povidone-iodine solution, evaluating the minimum inhibitory concentration and the effect of various microbial strains. Material and methods Our study included a group of 36 patients with 20 boys and 16 girls aged 16-20 years. The research consisted in laboratory and clinical investigations. At these patients we performed complete clinical examination, periodontal probing, radiographic examination, and microbial test for responsible flora. Results Our results showed that the reduction in the depth of the pockets and clinical attachment gain occurred, when the teeth have been treated with povidone - iodine in addition of hydrogen peroxide mixture, or with povidone -iodine and saline solution only as a coolant during the scaling ultrasound.